Analisis Pengaruh Fitur Live Streaming Shopping pada Platform Tiktok terhadap Keputusan Pembelian di Kalangan Mahasiswa Kota Bandung - Nurbani Shafira Rohmah Fadilah (International Journal Administration, Business & Organization, 2023)
The purpose of conducting this research is to determine the effect of Live Streaming Shopping Tiktok on purchasing decisions of Bandung city students. This study used a descriptive survey method by distributing questionnaires via g-form media to 102 respondents. The sample of this study is students who are currently carrying out their education in the city of Bandung with the criteria of having a Tiktok account and having watched Tiktok Live Streaming Shopping. Data processing was carried out using the Validity and Reliability test methods, Normality Test, Descriptive Analysis, Correlation Test and Simple Linear Regression Analysis. From this processing, it was found that Live Streaming Shopping had a positive effect on purchasing decisions of 53.2%.